ANALYSIS OF THE DELIPIDATION STAGE OF THE EXTRACTION OF CHITHIN FROM NATURAL SOURCES (Scientific journal of the Fergana State University, 2025)
During our research, we aimed to use some insects (Melolontha melolontha, Leptinotarsa ​​decemlinaeata, Eurygaster integriceps) as substitutes for raw materials used as a source of chitin in the world. In this, the classical method of chitin extraction was improved, that is, a delipidation stage was added to the general process based on the nature of our raw materials.It can be seen from the table above that the optimal conditions for the delipidation stage of natural raw materials are 1-1.5 hours for Melolontha melolontha, Leptinotarsa decemlinaeata, Eurygaster integriceps and a temperature of 60-80 ºC. The yield of the obtained products was 73.2%; 75.0%; 69.3%, depending on the sequence of raw materials.